DISEASES CAUSED BY BACTERIA OF THE AEROMONAS AND PSEUDOMONAS GENUS WHEN REARED FISH IN CONTROLLED SYSTEMS (Experimental biology, 2021)
Aquaculture represents a higher share of world fish supply and a strong influence on price formation in the sector overall (both production and trade). The total sale value of fisheries and aquaculture production in 2016 was estimated at USD 362 billion, of which USD 232 billion was from aquaculture production. Between 1961 and 2016, the average annual increase in global food fish consumption (3.2 percent) outpaced population growth (1.6 percent) and exceeded that of meat from all terrestrial animals combined (2.8 percent). By creating optimal growing conditions such as temperature, oxygen and hydrochemical regimes, the growth and sexual maturation of fish is significantly reduced, which contributes to the development of industrial aquaculture. However, the rapid development of aquaculture is accompanied by outbreaks of diseases caused by bacterial infection, which lead to high mortality and catastrophic economic losses. Mass outbreaks can occur suddenly under the influence of stress factors arising in connection with a sharp change in conditions of detention, as well as an increase in planting densities of rearing objects. The most severe bacterial diseases in aquaculture are infections caused by members of the Aeromonas and Pseudomonas genus. Bacteria of the Aeromonas and Pseudomonas genus are the causative agents of hemorrhagic septicemia (Aeromonas hydrophila, Pseudomonas fluorescens), furunculosis (Aeromonas salmonicida), which annually cause economic losses in aquaculture. Nowadays, due to widespread and often uncontrolled use of antibiotics, the number of bacteria resistant to antibiotics has increased dramatically and is the main cause of morbidity and mortality. This phenomenon can not only lead to the failure of antimicrobial therapy, but also raise concerns about the safety of fish products.This review examines the current data on fish diseases caused by bacteria of the Aeromonas and Pseudomonas genus, dominant virulence factors, problems of identification and antibiotic resistance.